Inherently radiopaque narrow-size-calibrated microspheres: proof of principle in a pig embolization model - Sommer, Christof-Matthias; Harms, Alexander; Do, Thuy; Gockner, T. L.; Kriegsmann, Mark; Schlett, Christopher L.; Holzer, Kerstin; Vollherbst, Dominik; Warth, Arne; Pereira, P. L.; Eichwald, V.; Jugold, M.; et al. (CardioVascular and interventional radiology, 2018)
Purpose. To investigate radiopacity, size and size calibration, morphology, and vascular distribution of inherently radiopaque microspheres in vitro and in a pig embolization model.Materials and MethodsWe compared three types of microspheres: DCBead™ (size 100-300 µm) and Embozene™ (250 µm) as clinically established microspheres, and the prototype Visible (250 µm) that contains additional radiopaque material. Size and size calibration of microspheres were examined by laser diffraction. Pulmonary artery embolization was performed in 12 pigs, and radiopacity was examined by in vitro micro-computed tomography (CT), in vivo cone-beam CT, and ex vivo micro-CT after killing. Morphology and vascular distribution of microspheres were microscopically examined.ResultsIn in vitro and ex vivo micro-CT, radiopacity of Visible was higher than that of Embozene™, whereas DCBead™ showed no radiopacity. In in vivo cone-beam CT, radiopacity was observed with Visible but not with Embozene™ and DCBead™. Laser diffraction revealed that 7.0% (Visible), 6.5% (Embozene™), and 22.5% (DCBead™) of microspheres were smaller than 223.5 μm. Visible and Embozene™ microspheres were very often located in bronchiolus-associated arteries, but rarely in subsegmental and capillary arteries, whereas DCBead™ were very often and often detected in bronchiolus-associated arteries and capillary arteries, respectively (and rarely in subsegmental arteries).ConclusionAfter pulmonary artery embolization, Visible but not Embozene™ or DCBead™ provide in vivo radiopacity in cone-beam CT. In contrast to non-narrow-size-calibrated DCBead™, pulmonary artery embolization with narrow-size-calibrated Visible and Embozene™ result in a predictable arterial distribution without embolization-related hemorrhagic lung infarction.